Selection and evaluation of lactic acid bacteria from chicken feces in Thailand as potential probiotics - Khurajog,Benjamas; Disastra,Yuda; Lawwyne,Lum Dau; Sirichokchatchawan,Wandee; Niyomtham,Waree; Yindee,Jitrapa; Hampson,David John; Prapasarakul,Nuvee (PeerJ, 2023)
Background Lactic acid bacteria (LAB) are widely used as probiotics in poultry production due to their resilience to low pH and high bile salt concentrations, as well as their beneficial effects on growth performance and antagonistic activity against enteric pathogens. However, the efficacy of probiotics depends on strain selection and their ability to colonize the host’s intestine. This study aimed to select, identify, and evaluate LAB strains isolated from chicken feces in Thailand for potential use as probiotics in the chicken industry. Methods LAB strains were isolated from 58 pooled fresh fecal samples collected from chicken farms in various regions of Thailand, including commercial and backyard farms. Gram-positive rods or cocci with catalase-negative characteristics from colonies showing a clear zone on MRS agar supplemented with 0.5% CaCO3 were identified using MALDI-TOF mass spectrometry. The LAB isolates were evaluated for acid (pH 2.5 and pH 4.5) and bile salt (0.3% and 0.7%) tolerance. Additionally, their cell surface properties, resistance to phenol, antimicrobial activity, hemolytic activity, and presence of antimicrobial resistance genes were determined. Results A total of 91 LAB isolates belonging to the Pediococcus, Ligilactobacillus, Limosilactobacillus, and Lactobacillus genera were obtained from chicken feces samples. Backyard farm feces exhibited a greater LAB diversity compared to commercial chickens. Five strains, including Ligilactobacillus salivarius BF12 and Pediococcus acidilactici BF9, BF14, BYF20, and BYF26, were selected based on their high tolerance to acid, bile salts, and phenol. L. salivarius BF12 and P. acidilactici BF14 demonstrated strong adhesion ability. The five LAB isolates exhibited significant cell-cell interactions (auto-aggregation) and co-aggregation with Salmonella. All five LAB isolates showed varying degrees of antimicrobial activity against Salmonella strains, with P. acidilactici BYF20 displaying the highest activity. None of the LAB isolates exhibited beta-hemolytic activity. Whole genome analysis showed that L. salivarius BF12 contained ermC, tetL, and tetM, whereas P. acidilactici strains BF9 and BF14 carried ermB, lnuA, and tetM. Conclusion The selected LAB isolates exhibited basic probiotic characteristics, although some limitations were observed in terms of adhesion ability and the presence of antibiotic resistance genes, requiring further investigation into their genetic location. Future studies will focus on developing a probiotic prototype encapsulation for application in the chicken industry, followed by in vivo evaluations of probiotic efficacy.
Keywords: Chicken; Lactic acid bacteria; Probiotics; Thailand